2014
DOI: 10.1111/cas.12454
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐β‐induced lncRNA‐Smad7 inhibits apoptosis of mouse breast cancer JygMC(A) cells

Abstract: Transforming growth factor (TGF)-β exhibits both pro-apoptotic and anti-apoptotic effects on epithelial cells in a context-dependent manner. The anti-apoptotic function of TGF-β is mediated by several downstream regulatory mechanisms, and has been implicated in the tumor-progressive phenotype of breast cancer cells. We conducted RNA sequencing of mouse mammary gland epithelial (NMuMG) cells and identified a long non-coding RNA, termed lncRNA-Smad7, which has anti-apoptotic functions, as a target of TGF-β. lncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 32 publications
3
68
0
Order By: Relevance
“…In addition, MSK1 [74], Dlx2 [75], and lncRNA-Smad7 [76] have also been shown to have effects on anti-TGF-β-induced apoptosis but their expression levels are also elevated during TGF-β-induced apoptosis and EMT. Thus, it can be concluded that the level of anti-apoptotic molecules determines the proportion of cells to survive or to undergo EMT in response to TGF-β stimulation.…”
Section: The Balance Between Tgf-β-induced Apoptosis and Emt And Its mentioning
confidence: 99%
“…In addition, MSK1 [74], Dlx2 [75], and lncRNA-Smad7 [76] have also been shown to have effects on anti-TGF-β-induced apoptosis but their expression levels are also elevated during TGF-β-induced apoptosis and EMT. Thus, it can be concluded that the level of anti-apoptotic molecules determines the proportion of cells to survive or to undergo EMT in response to TGF-β stimulation.…”
Section: The Balance Between Tgf-β-induced Apoptosis and Emt And Its mentioning
confidence: 99%
“…It has been shown that lncRNA plays an important role in multiple molecule regulation, such as transcriptional regulation, post-transcriptional regulation, and modification [8][9][10]. For example, lncRNA GAS5 is down-regulated in NSCLC tissues and cells, and negatively correlated with miR-23a, which inhibits the occurrence of NSCLC [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to well-studied small ncRNA, such as miRNAs, siRNAs, and piRNAs, LncRNAs are less well characterized. Nowadays, increasing number of studies shows that LncRNAs play important roles in cancer progression and metastasis as well as cellular processes, such as cell proliferation and apoptosis [16][17][18]. Therefore, identifying the relationship between LncRNAs and hyperlipidemia-induced apoptosis of HUVECs may help understand the function of clopidogrel treatment in patients with CVD.…”
Section: Introductionmentioning
confidence: 99%